EFFECT OF SURFACE TREATMENT TO BOND STRENGTH OF SILICONE SOFT DENTURE LINING TO HEATCURED ACRYLIC RESIN DENTURE BASE - Febriani,; Syafrinani,; Agusnar, Harry; Ariyani, (International Journal of Psychosocial Rehabilitation, 2020)
Silicone soft denture lining (SDL) material as a part of SDL is defined by ISO as a soft resilient material bonded to the fitting surface of the denture to reduce trauma to the supporting tissue. Silicone SDL nowdays have been famous as an obturator bulb of heatcured acrylic resin (PMMA) denture base because of soft permanently and biocompatibility properties which can be used to add the retention and stability of definitive obturator for patient with severe undercut palatal defect without giving the painfull. The only weakness of silicone SDL is bond failure to PMMA that make microleakage created an environment for potential bacterial growth. Bond failure can be solved by surface treatment. Purpose : The aim of this study were to evaluate the effects of 3 different surface treatments (sandblasting, primer adhesive and sandblasting-primer adhesive combination) on bond strength of 2 kinds of silicone SDL (autopolymerized silicone SDL and heatpolymerized silicone SDL) to PMMA denture base. Methods : The 3 mm thickness of silicone SDL were processed between 2 PMMA blocks became one specimens (n=40). The bond strength of 40 specimen of PMMA-Silicone SDL were measured by tensile test with universal testing machine at a crosshead speed of 5 mm/min until failure was detected. The bond strength (MPa) was calculated by dividing the maximum tensile strength value with cross-sectional area. T-test, ANOVA and LSD tests were used to analyze the data (α=0.05). The bond strength value were analyzed with types of failure (adhesive, cohesive and mixed failure) and morphology view of PMMA surface by a single operator. Result : PMMA- heatpolymerized silicone SDL with or without surface treatment were the higher significance bond strength than PMMA-autopolymerized silicone with or without surface treatment. All of the surface treatment can be increase the bond strength either to PMMA-autopolymerized Silicone SDL or to PMMA-heatpolymerized Silicone SDL. The significance effect of surface treatment is Primer adhesive either to PMMA-autopolymerized silicone SDL or to PMMA-heatpolymerized silicone SDL. Conclusion Primer adhesive gave the highest significance effect to PMMA- heatpolymerized silicone SDL characterized either with highest bond strength values, cohesive failures and highest roughened surfaces of PMMA interface.